2015
DOI: 10.1055/s-0035-1545798
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Trabecular Micro-Bypass Stent Combined with Phacoemulsification Compared to Phacoemulsification Alone

Abstract: iStent implantation resulted in similar IOP reduction to phacoemulsification alone but achieved a significantly greater reduction in glaucoma medications. This may improve compliance and quality of life, and reduce health care costs in patients with early to moderate glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 4 publications
2
23
0
Order By: Relevance
“…Within a whole eye perfusion model, IOP decreased by 6.0 mmHg from baseline with a single iStent and decreased by an additional 2.9 mmHg with a second iStent, for a total IOP reduction of 8.9 mmHg from baseline [47]. Echoing these preclinical findings, a prospective clinical trial compared 3.5-year results of one, two, or three iStents implanted in a sole procedure [30], while two other studies analyzed two or three iStents with concomitant cataract surgery [48,49]. These three studies confirmed that while the first stent produces the majority of IOP reduction, additional stents enable further reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Within a whole eye perfusion model, IOP decreased by 6.0 mmHg from baseline with a single iStent and decreased by an additional 2.9 mmHg with a second iStent, for a total IOP reduction of 8.9 mmHg from baseline [47]. Echoing these preclinical findings, a prospective clinical trial compared 3.5-year results of one, two, or three iStents implanted in a sole procedure [30], while two other studies analyzed two or three iStents with concomitant cataract surgery [48,49]. These three studies confirmed that while the first stent produces the majority of IOP reduction, additional stents enable further reduction.…”
Section: Discussionmentioning
confidence: 99%
“…On the clinical side, a prospective randomized trial by Katz et al compared long-term outcomes following implantation of one, two, and three iStents in a standalone procedure, and Belovay et al and El Wardani et al evaluated two or three iStents combined with cataract surgery [33,56,57]. All three clinical studies demonstrated that the majority of IOP reduction occurs after the first stent and that additional stents produce further IOP reduction, likely due to access to more regions of the distal outflow network and increased probability of stenting areas of Schlemm's canal that are still patent and functional.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of IOP reduction, the patient outcomes were comparable to published results of surgeons' early cases of combined phacoemulsification and iStent insertion. [6][7][8][9][10] This suggests that our residents' performance was not inferior to that of other surgeons new to the procedure. While the focus of this article is not the efficacy of the iStent, these patient outcomes support the promising results of our curriculum.…”
Section: Discussionmentioning
confidence: 77%